Fast update method of new equipment status in IMS network based on ant colony optimization algorithm. Issue 1 (June 2021) - Sun, Lili; Zhai, Hongting; Zhai, Qi; Li, Liang; Zhang, Qingrui
Abstract: In order to update the status of new equipments in IMS network quickly, a new method based on ant colony optimization algorithm is studied. This method is to lock the new status of IMS network and establish the location model of new equipment in IMS network. For the new equipment in IMS network that has been located, the load balancing method of new equipment in IMS network based on ant colony optimization algorithm is adopted to obtain the optimal operation state of new equipment in IMS network, and realize the rapid update of new equipment status in IMS network. The experimental results show that: the proposed method can accurately locate the coordinates of new equipments in IMS network when the node regularity is significant or not; it can effectively improve the update speed of new equipments in IMS network, and realize the rapid update of new equipment status in IMS network; the negative impact on IMS network is smaller, and under the premise of small and large load of IMS network, the proposed method can improve the performance of IMS network. When the new IMS network adds new equipment status, the false alarm rate is small and the update result is reliable.